2013
DOI: 10.1007/s12291-012-0294-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of Hormone Receptors and Epidermal Growth Factor Expression in Invasive Breast Cancers in a Cohort of Western India

Abstract: The objective of study was to evaluate and correlate the pathological characteristics of breast cancer patients with estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (Her2/neu) detected by immunohistochemistry and/or fluorescent in situ hybridization method. We have conducted 2 year study of 204 cases of breast cancer at HCG-Medisurge Hospitals, Ahmedabad from 2009 to 2011. Significant correlation was found in ER and PR expression whereas no correlation was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
8
9
1
Order By: Relevance
“…There was significant correlation seen between the age of the patient and ER (p = 0.000) & PR (p = 0.000) expression in present study. Studies by Dodiya H et al [19] and Ghosh S et al [20] showed similar results. Significant correlation was also observed between age of the patient and HER2/neu expression (p = 0.000), similar to studies conducted by Ramic S et al [21] and Ganesan M et al [22] Axillary Lymph Node Status 38% patients had axillary lymph nodes positive for metastasis.…”
Section: Agesupporting
confidence: 56%
“…There was significant correlation seen between the age of the patient and ER (p = 0.000) & PR (p = 0.000) expression in present study. Studies by Dodiya H et al [19] and Ghosh S et al [20] showed similar results. Significant correlation was also observed between age of the patient and HER2/neu expression (p = 0.000), similar to studies conducted by Ramic S et al [21] and Ganesan M et al [22] Axillary Lymph Node Status 38% patients had axillary lymph nodes positive for metastasis.…”
Section: Agesupporting
confidence: 56%
“…[38] In presnt study, there was seen significant correlation tumor grade with ER(p value=0.003) & PR(p value=0.031), study done by Thoreson S et al, [39] Onitilo AA et al, [14] and Dodiya H et al showed similar results. [29] No significant association was seen between tumor grade and HER2/neu expression (p value=0.298) in present study. Study conducted by Naeem M et al, [40] and Dodiya H et al showed similar results.…”
Section: Subtype4contrasting
confidence: 61%
“…In the present study, there was seen significant correlation between age of the patient and ER (p value=0.000), PR (p value=0.000) and HER2/neu (p value=0.000) expression in present study. Studies by Desai SB et al, [28] Dodiya H et al, [29] Thang VH et al, [30] and Ganesan M et al, [31] showed similar results. The majority of receptors positive cases were postmenopausal in our study.…”
Section: Subtype4mentioning
confidence: 54%
See 1 more Smart Citation
“…Breast cancer is the commonest cancer in women worldwide, including Nigeria [1]. The cancer is also associated with a high mortality, especially when the patient presents at a late stage and has a high grade disease [2].…”
Section: Introductionmentioning
confidence: 99%